PRACTICE OF SELF-MEDICATION AND QUALITY OF LIFE ASSESSMENT AMONG HEALTHCARE WORKERS OF A TERTIARY HOSPITAL IN ASSAM DURING COVID-19 PANDEMIC - DEKA, SIDDHARTHA KRISHNA; BORAH, LAKHIMI; SARMAH, RIPUNJOY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aims of this study were to collect sociodemographic, clinical data regarding practice of self-medication and to assess quality of life in healthcare workers involved taking care of COVID-19 patients. Methods: The study population consisted of 104 healthcare workers from Gauhati Medical College and Hospital directly involved in management and control of COVID-19 Pandemic. It was a cross-sectional observational study using non-probability sampling. Data were collected in a questionnaire developed by the investigators which included age, sex, and occupation, COVID-19 such as symptoms, medicines used, contraction and confirmation of COVID-19 positive, and self-medication when COVID positive, symptomatic relief, and adverse effects and usefulness of self-medication. The data for mental health were obtained in a questionnaire based on the Professional Quality of Life Scale (Compassion Satisfaction and Compassion Fatigue Version 5) with responses rated on a five-point Likert scale. Results: The study consisted of 104 participants. Males were n=42 (40%) and females were n=62 (60%). Doctors n=20 (19%), Laboratory Technicians n=22 (21%), Nurses n=44 (42%), Pharmacists n=13 (13%), Ward boys n=3 (3%), and Ward girls n=2 (2%) took part. Eighty-four (97.7%) respondents took paracetamol, 39 (45.3%) took cough syrup, 30 (34.9%) used nasal decongestants, 25 (29.1%) utilized throat gargle, 24 (27.9%) used azithromycin, 22 (25.6%) used cefixime, 13 (15.1%) took amoxyclav, 27 (31.4%) took ORS, 3 (3.5%) took Doxycycline, 4 (4.8%) used Ivermectin, 1 (1.2%) took Dexamethasone, and 1 (1.2%) used Multivitamin. About 68% (n=51) of COVID Positive respondents self-medicated with Azithromycin, 24% (n=18) with Ivermectin, 41.3% (n=31) with Doxycycline, 20% (n=15) with Dexamethasone, and 4% (n=3) with Levocetrizine and Paracetamol. The Mental Health Assessment Scores were obtained as the sum total of scores of answers to the 30 questions provided per respondent. About 7% (n=7) respondents with total score between 60 and 69, 12% (n=13) from 70 to 79, 29% (n=30) from 80 to 89, 22% (n=23) from 90 to 99, 16% (n=17) from 100 to 109, 13% (n=13) from 110 to 119, and 1% (n=1) between 120 and 129. This indicates that some participants had mild burnout, most had moderate burnout, and a few had severe burnout. Conclusion: Self-medication practices common among healthcare workers, increased during the COVID-19 Pandemic which must be appropriately managed to stay away from the ill effects. Providing adequate mental health resources and education to the affected health workers will motivate them increasing their productivity during the pandemic.